2019
DOI: 10.1039/c9ay00007k
|View full text |Cite
|
Sign up to set email alerts
|

An effective approach to the quantitative analysis of skin-whitening agents in cosmetics with different substrates based on conventional UV-Vis determination

Abstract: Tchebichef curve moment approach was proposed for the quantitative analysis of five skin-whitening agents in cosmetics, which extended effectively the application of conventional UV-Vis determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
7
0
3
Order By: Relevance
“…The dialysis bag with mixture solution (20 mL) was immersed in phosphate buffer (1000 mL) and incubated at 25 °C with stirring for 1 h to remove free NA. The concentration of NA was assayed using an ultraviolet spectrophotometer at 262 nm 10 . Encapsulation efficiency (EE) and the drug loading capacity (DLC) of the vesicles were evaluated according to the following equations: EE0.25em()%=M1M2M1×100 DLC0.25em()%=M1M2M3×100 where M 1 is the weight of NA added, M 2 is the weight of free NA and M 3 is the weight of mixture (SO, CMC and loaded encapsulated NA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dialysis bag with mixture solution (20 mL) was immersed in phosphate buffer (1000 mL) and incubated at 25 °C with stirring for 1 h to remove free NA. The concentration of NA was assayed using an ultraviolet spectrophotometer at 262 nm 10 . Encapsulation efficiency (EE) and the drug loading capacity (DLC) of the vesicles were evaluated according to the following equations: EE0.25em()%=M1M2M1×100 DLC0.25em()%=M1M2M3×100 where M 1 is the weight of NA added, M 2 is the weight of free NA and M 3 is the weight of mixture (SO, CMC and loaded encapsulated NA).…”
Section: Methodsmentioning
confidence: 99%
“…It is known to exert skin‐lightening effects by limiting the transfer of melanosomes from melanocytes to the surrounding keratinocytes 9 . NA has fewer side effects than hydroquinone, and is safer than other whitening ingredients 10 . The efficacy of NA has been proven in several clinical studies, in which NA was shown to be an effective skin‐whitening agent 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…This data set was derived from ref which consisted of 36 mixture samples of arbutin (AR), niacinamide (NA), kojic acid (KA), hydroquinone (HQ), and phenol (PHE). The UV–vis system provided a matrix with a size of 36 (the number of mixture samples) × 132 (wavelength data points).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Cosmetic dermatology preparations such as bleaching agents (Khezri, Saeedi, & Dizaj, 2018) are ingredients with skin‐related biological activities for increasing and improving skin beauty (Kusumawati & Indrayanto, 2013). The main function of skin whitening preparations is the treatment of skin hyperpigmentation disorders through increase in skin‐bleaching (Li, Yin, Zhai, Lu, & Mi, 2019). The possibility of controlling skin hyperpigmentation disorders (especially in the face and neck) is a most cosmetically important research aim (Napolitano & Ito, 2018).…”
Section: Introductionmentioning
confidence: 99%